The acceleration and deceleration profiles of elite female soccer players during competitive matches. Issue 9 (September 2017) - Mara, Jocelyn K.; Thompson, Kevin G.; Pumpa, Kate L.; Morgan, Stuart
Abstract: Objectives: The aim of this study was to determine the acceleration (≥2 m s −2 ) and deceleration (≤ − 2 m s −2 ) profiles of elite female soccer players during competitive matches. Design: Single cohort, observational study. Methods: An Optical Player Tracking system was used to determine acceleration (≥2 m s −2 ) and deceleration (≤ − 2 m s −2 ) variables for twelve elite female players across seven competitive matches. Results: In total, players performed 423 (±126) accelerations and 430 (±125) decelerations per match. It was shown that the number of accelerations (p = 0.003–0.034, partial η 2 = 0.229–321) and decelerations (p = 0.012–0.031, partial η 2 = 0.233–275) at different intensities (based on the start and final velocity) varied according to player position. Mean and maximum distance per effort was 1–4 m and 2–8 m, respectively, and differed between each intensity category (p < 0.001, partial η 2 = 0.753–0.908). The mean time between efforts was 14 s for both accelerations (±5 s) and decelerations (±4 s) and fluctuated between 15 min time periods (p < 0.001, partial η 2 = 0.148–0.206). Conclusions: The acceleration and deceleration profiles varied according to player position and time period of the match. The results of this study can be used to design match-specific acceleration and deceleration drills to enhance change of speed ability.